A new species of Hypericum section Olympia (Hypericaceae) from Central Greece - Zografidis, Aris; Cheminal, Alexian; Dimopoulos, Panayotis (Phytotaxa, 2024)
Hypericum intricatum, discovered in an ophiolitic area near the city of Domokos, Central Greece, is here described and illustrated as a species new to science. It belongs to section Olympia, as indicated by nuclear ribosomal ITS phylogeny, congruent with several but not all key morphological characters of this taxon. The sole known population of the new species is critically small and restricted to a floristically noteworthy spot accompanied by other rare and threatened serpentine-specialist species.